Presence of nuclei carrying a recessive lethal gene in a wild isolate of Neurospora - Alka Pandit; Bhuvana Kannan; Ramesh Maheshwari (Fungal Genetics Reports, 1994)
This study shows that a recessive lethal gene has arisen and persists in wild-collected Neurospora but is masked in the heterokaryotic mycelium until it segregates in the spores.